Spectrophotometric determination of Zinc(II) in solutions samples using 1-azobenzene-3-(3-hydroxyl-2-pyridyl)-triazene in the Surkhandarya region (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this paper has been studied a new sensitive and selective chromogenic reagent, 1-azobenzene-3-(3-hydroxyl-2-pyridyl)-triazene (ABHPT), was synthesized. It has been found that reacts with zinc (II) in a borax buffer solution (pH 10.0) to form 2: 1 red complexes with the maximum absorption at 530 nm. The apparent molar absorptivity of the complex is 2.6 × 105 L/(mol cm). A new method for the spectrophotometric determination of trace Zinc(II) was developed. Beer’s law is obeyed for 0–15 μg of zinc (II) in 25 mL of solution. The limit of quantification, limit of detection, and relative standard deviation are 0.74 ng/mL, 0.25 ng/mL, and 1.0%, respectively.